Promoting successful participation of people living with Alzheimer's disease and related dementias in pain-related neuroimaging research studies - Iversen, Wm. Larkin; Monroe, Todd B.; Atalla, Sebastian; Anderson, Alison R.; Cowan, Ronald L.; Wright, Kathy D.; Failla, Michelle D.; Moss, Karen O. (Frontiers in Pain Research, 2022)
Recruitment and retention of participants for pain-related neuroimaging research is challenging and becomes increasingly so when research participants have a diagnosis of Alzheimer's disease and related dementias (ADRD). This article shares the authors' recommendations from several years of successful recruitment and completion of pain-related neuroimaging studies of people living with ADRD and includes supportive literature. While not an exhaustive list, this review covers several topics related to recruitment and retention of participants living with ADRD, including community engagement, capacity to consent, dementia diagnostic criteria, pain medication and other study exclusion criteria, participant and caregiver burden, communication concerns, and relationships with neuroimaging facilities. Threaded throughout the paper are important cultural considerations. Additionally, we discuss implications of the coronavirus (COVID-19) pandemic for recruitment. Once tailored to specific research study protocols, these proven strategies may assist researchers with successfully recruiting and retaining participants living with ADRD for pain-related neuroimaging research studies toward improving overall health outcomes.